28.2k views
5 votes
Find a formula for the sum of n terms. Use the formula to find the limit as n → [infinity]. lim n → [infinity] n 2 + i n 8 n i = 1

User Crystle
by
4.3k points

1 Answer

5 votes

Complete Question

Find a formula for the sum of n terms.
\sum\limits_(i=1)^n ( 8 + (i)/(n) )((2)/(n) )

Use the formula to find the limit as
n \to \infty

Answer:


K_n = (n + 73 )/(n)


\lim_(n \to \infty) K_n = 1

Explanation:

So let assume that


K_n = \sum\limits_(i=1)^n ( 8 + (i)/(n) )((2)/(n) )

=>
K_n = \sum\limits_(i=1)^n ( (16)/(n) + (2i)/(n^2) )

=>
K_n = (2)/(n) \sum\limits_(i=1)^n (8) + (2)/(n^2) \sum\limits_(i=1)^n(i)

Generally


\sum\limits_(i=1)^n (k) = (1)/(2) n (n + 1)

So


\sum\limits_(i=1)^n (8) = (1)/(2) * 8* (8 + 1)


\sum\limits_(i=1)^n (8) = 36


K_n = (2)/(n) \sum\limits_(i=1)^n (8) + (2)/(n^2) \sum\limits_(i=1)^n(i)

and


\sum\limits_(i=1)^n (i) = (1)/(2) n (n + 1)

Therefore


K_n = (72)/(n) + (2)/(n^2) * (1)/(2) n (n + 1 )


K_n = (72)/(n) + (1)/(n) (n + 1 )


K_n = (72)/(n) + 1 + (1)/(n)


K_n = (72 + 1 + n )/(n)


K_n = (n + 73 )/(n)

Now
\lim_(n \to \infty) K_n = \lim_(n \to \infty) [(n + 73 )/(n) ]

=>
\lim_(n \to \infty) [(n + 73 )/(n) ] = \lim_(n \to \infty) [(n)/(n) + (73 )/(n) ]

=>
\lim_(n \to \infty) [(n + 73 )/(n) ] = \lim_(n \to \infty) [1 + (73 )/(n) ]

=>
\lim_(n \to \infty) [(n + 73 )/(n) ] = \lim_(n \to \infty) [1 ] + \lim_(n \to \infty) [(73 )/(n) ]

=>
\lim_(n \to \infty) [(n + 73 )/(n) ] = 1 + 0

Therefore


\lim_(n \to \infty) K_n = 1

User MoRe
by
4.9k points